Evaluation of The Success of Zirconia Implants (ISSA-NZI) And Marginal Bone Level After A Year of Functional loading (Journal of Hama University, 2022)
the aim of this study is to evaluate the marginal bone loss (MBL) around zirconia implants that were used for the replace a missed single tooth. 12 locally manufactured zirconia implants (ISSA-NZI, one-piece implant) installed in the jawbones of patients who need to replace a missing posterior tooth, after two months for the mandible and four months for the maxilla, we crowned the abutments with zirconia crowns , and monitoring radiographs were taken after (1, 2, 3, 4, 6, 9, 12 and 14 months) of implantation. By this technique of x- ray photos, bone absorption peri- implants was evaluated, and averages of absorption values were recorded during the observation periodThe success rate of zirconia implants was 93%, the average of (MBL) after one year of rehabilitation was 1.03mm with (SD = ±0.05 mm) of the mesial side and 1.07 mm with (SD = ±0.07 mm) of the distal side The (MBL) of one-piece zirconia implants (ISSA-N.Z.I) is within clinically acceptable limits.